The miracles impact of inflation rates on stock market returns volatility evidence from Asia: Developing countries Vs Developed countries / Aripuddin Bin Ambo - Ambo, Aripuddin (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2012)
This paper aims to examine the relationship between inflation and the stock market return volatility. In financial market, the condition of stock market return volatility is the major concern among investors as it brings the investment risk. In this study, we use Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model to estimate the volatility return of stock market for each given country. The impact of inflation rate has been investigated in order to know either there is predictive power for stock market volatility in Six Asian countries. The findings suggest that impact of inflation rate on the stock market could be both the positive and negative relationship depends on the market environment. We found that our empirical results show all the developed countries which are Singapore, Japan, and Korea have negative relationships between inflation rate and stock market returns volatility while most of developing countries that we tested show positive relationships except for India. Countries with the higher the rate of inflation relatively has greater stock market volatility where the risk is greater in the market.